Libro De Actas CIT2016. XII Congreso De Ingeniería Del Transporte 2016
DOI: 10.4995/cit2016.2016.4214
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Study of the Effect of Decreasing Truck Traffic Flow on Safety on Almeria-Barcelona Corridor

Abstract: In this paper the effect of truck traffic on road safety has been analyzed through simulation study. The main objective of the study is to quantify the effect of the decreasing average annual daily traffic of heavy duty vehicles (trucks) on road safety. As the road safety indicators the frequency road accidents is considered. The data used in the study were collected from one of the most crowded routes in Spain which connects Almeria (southeast) with Barcelona (northeast). The observed data covers year 2010 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…It mainly evaluates road safety performance based on traffic data to predict the type of collision [6] and the severity of accidents, to implement safety control measures, which is of great significance in preventing traffic accidents. At the same time, fine-grained truck flow data can be applied to support passenger and truck separation strategies [7], and predict the speed of traffic and the number of traffic accidents [8], [9]. It can be concluded that the application of truck flow data to freeway risk assessment will yield considerable improvements.…”
Section: Introductionmentioning
confidence: 99%
“…It mainly evaluates road safety performance based on traffic data to predict the type of collision [6] and the severity of accidents, to implement safety control measures, which is of great significance in preventing traffic accidents. At the same time, fine-grained truck flow data can be applied to support passenger and truck separation strategies [7], and predict the speed of traffic and the number of traffic accidents [8], [9]. It can be concluded that the application of truck flow data to freeway risk assessment will yield considerable improvements.…”
Section: Introductionmentioning
confidence: 99%